PENGARUH PUPUK AKAR (NPK) DENGAN PUPUK DAUN (MULTIMIKRO) DAN ZAT PENGATUR TUMBUH (ETHREL) TERHADAP PERTUMBUHAN VEGETATIF TANAMAN LADA - Mulyono, Daru (Badan Pengkajian dan Penerapan Teknologi, 2009)
The objective of the research was to investigate the effect of root fertilizers NPK (Nitrogen, Phospor, and Potassium) combined with leaf fertilizer (Multimikro) and Growth Regulating Substance (Ethrel) to the vegetative growth of pepper plants. Theresults of the research showed that the use of root fertilizers NPK (dosage: 2.5; 5.0; and 10.0 g/plant) increased the plants height of 12,0 cm, 19,8 cm, and 23,1 cm respectively. The use of root fertilizers NPK (dosage: 2.5; 5.0; and 10.0 g/plant) combined with leaf fertilizer Multimikro (dosage 1.5 ml/l) increased plant height significantly 15.4 cm, 23.3 cm, and 26.9 cm respectively. Moreover, the use of root fertilizer NPK (dosage: 2.5; 5.0; and 10.0 g/plant) combined with Growth Regulating Substance Ethrel (dosage 1.5 ml/l) increased the vegetative growth of pepper plants significantly to a high of 18.4 cm, 28.4 cm, and 32.5 cm respectively. Conclution of the research indicated that the combination between NPK fertilizer and Ethrel was better than the combination between NPK fertilizer and Multimikro to the vegetative growth of pepper plants.